Land consolidation as technical change: Economic impacts in rural Vietnam. (March 2020) - Nguyen, Huy Quynh; Warr, Peter
Highlights: It is well established that land fragmentation reduces the productivity of on-farm labor. The literature is confused about how it affects the amount of labor used on-farm and off-farm. This paper shows the conceptual benefit of viewing land consolidation as a form of technical change. Empirical results for Vietnam confirm that land consolidation reduces use of on-farm labor and increases off-farm use. Land consolidation also promotes the adoption of mechanization. Abstract: This paper deepens the economic analysis of the effects of land consolidation – reduction of land fragmentation. It does this in the context of rural Vietnam, studying whether land consolidation promotes or hinders the Vietnamese government's policy objectives of encouraging agricultural mechanization and stimulating the off-farm rural economy. The analysis views land consolidation as a form of technical change, making it possible to apply the rich insights developed in the economic literature on that subject. This treatment reveals that the economic impacts of land consolidation depend partly on its factor bias and partly on the degree to which labor is substitutable in production for other factors. At a theoretical level, if a technical change is factor neutral, it will reduce off-farm labor supply and slow rural structural transformation away from agriculture; if it is labor-augmenting and the elasticity of substitution between factors is low enough, the opposite effects are predicted. The paper studies these issues empirically for rice production in Vietnam, focusing on the impact that consolidation of rice land has on rice production, machinery use, and labor allocation. The findings confirm that land consolidation raises both farm productivity and farm income and stimulates increased machinery use. It also reduces farm labor supply, lowers labor intensity in farming, and thereby releases more farm labor to off-farm development, consistent with government policy objectives. Based on these findings, the paper concludes that land consolidation should be encouraged through development of land ownership rights and the promotion of land rental markets.